Marketing Strategy Analysis to Increase the Competitiveness of MSMEs (Study on the Pasundan Honey Bee Forest Farmer Group) - Ramdhani, Ahmad; Mulyana, Nana Setiya; Tribumela3, Maulana Lingga; Yunus, Wandiyana; Martiana, Astrina (SINTESA, 2024)
The marketing strategy represents a pivotal methodology employed to attain a sustainable competitive advantage for both manufacturers of goods and providers of services. This strategy serves as a foundational element in the formulation of a comprehensive corporate plan. In light of the complex challenges encountered by organizations, it is imperative to establish a holistic plan that can effectively guide each segment of the enterprise in executing its operational activities. Furthermore, the intensifying competition among firms across various sectors accentuates the necessity for effective marketing strategies. The primary objective of this study is to attain a greater understanding of marketing strategies that enhance competitiveness, as well as to evaluate the effectiveness of the marketing strategies that have been previously implemented. This research was conducted at the Kelompok Tani Hutan (KTH) Lebah Madu Pasundan, utilizing data collection methods that included documentation, interviews, and observations, while adopting a descriptive qualitative research approach. The findings from the analysis of marketing strategy effectiveness indicate a year-over-year increase in total sales, which can serve as a reliable reference for assessing the effectiveness of marketing strategies in navigating competition among honey producers